2020
DOI: 10.1159/000510109
|View full text |Cite
|
Sign up to set email alerts
|

Microelectrode Recording and Radiofrequency Thalamotomy following Focused Ultrasound Thalamotomy

Abstract: Magnetic resonance imaging-guided focused ultrasound (MRgFUS) is a novel method for stereotactic brain lesioning and has primarily been applied for thalamotomies to treat essential tremor (ET). The electrophysiological properties of previously MRgFUS-sonicated thalamic neurons have not yet been described. We report on an ET patient who underwent an MRgFUS thalamotomy but experienced tremor recurrence. We expanded the MRgFUS-induced thalamic cavity using radiofrequency (RF), with good effect on the tremor but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Some factors influencing this type of recurrence, which can also be partially considered a "loss of efficacy, " involve demographic factors, primarily the underlying pathology, where tremor recurrence is more frequent in patients affected by Parkinson's disease (PD) or long-standing essential tremor (ET) before developing PD symptoms. In our cases with early recurrence, however, only two were affected by PD (1,2,5,6,(12)(13)(14).…”
Section: Discussionmentioning
confidence: 61%
“…Some factors influencing this type of recurrence, which can also be partially considered a "loss of efficacy, " involve demographic factors, primarily the underlying pathology, where tremor recurrence is more frequent in patients affected by Parkinson's disease (PD) or long-standing essential tremor (ET) before developing PD symptoms. In our cases with early recurrence, however, only two were affected by PD (1,2,5,6,(12)(13)(14).…”
Section: Discussionmentioning
confidence: 61%
“…De Vloo et al used the opportunity to perform microelectrode recording in a patient who underwent unsuccessful MRgHiFUS treatment reaching only subtherapeutic temperatures. They found normal cell activity and argued, that this finding supports the expectation of not harming brain tissue below a threshold of 55°C ( 10 ). Dallapiazza et al compared the results of DBS, MRgHiFUS, GKRS and RFA in a systematic review and found evidence, that indeed the use different technologies in the same targets leads to comparable results ( 11 ).…”
Section: Consensus Statementmentioning
confidence: 85%
“…Instead, recent autopsy studies have reported that the thalamus lesion by MRgFUS was characterized by many foamy macrophages, immunoreactive for CD68 and less for IBA-1, but relatively preserved neurons compared to the adjacent thalamus [19]. In some recurrence cases after MRgFUS thalamotomy, re-ablation or DBS implantation in these patients can still improve their tremor performance again [20][21][22]. Despite all the above reasons, ignoring the of the disease pathophysiology and the biological features is just an illusion of excitement brought about by technological advance.…”
Section: Discussionmentioning
confidence: 99%